A Model of Character Development for Santri: The Role of Ethical Leadership, Value Development, and Character-Based Learning Mediated by Students’ Experiences - Nuryadi, Syafaat; Prayitno, Irwan; Kumoro, Dwi Ferdiyatmoko Cahya; Sukirman (International Journal of Social and Management Studies, 2025)
This study explores the role of ethical leadership, value development, and character-based learning in the character development of santri (students) in Islamic boarding schools (pesantren). Using a qualitative research design, this study seeks to develop a comprehensive model that integrates these elements, mediated by students' personal experiences, to enhance moral and ethical growth. Data were collected through semi-structured interviews, focus group discussions, and participant observation across three pesantren in Indonesia, involving a total of 30-40 participants, including santri and educators. Thematic analysis revealed that ethical leadership significantly influences students' behavior and moral decision-making, while value development fosters internalization of core ethical principles such as integrity, social responsibility, and empathy. Furthermore, character-based learning—embedded in daily practices, religious rituals, and communal activities—plays a crucial role in developing self-discipline and ethical behavior. Students' personal experiences, shaped by mentorship and community interactions, mediate these processes, further enhancing character formation. The study proposes a holistic model for character development in pesantren, emphasizing the interconnectedness of leadership, value development, and experiential learning. The findings offer theoretical, practical, and managerial implications for improving character education in Islamic educational settings, contributing to the global discourse on moral formation in educational contexts.